Prevalence, associated factors and impact of mild cognitive impairment in hospitalized older adults with Parkinson’s disease: a cross-sectional study - Gong, Siyuan; Wang, Tianqi; Tang, Rongzhu; Hu, Wangjuan; Wang, Wenjing; Li, Jia; Liu, Jihong; Liao, Chunlian (Frontiers in Aging Neuroscience, 2025)
BackgroundEarly identification of mild cognitive impairment (MCI) and timely interventions are essential to delay dementia in Parkinson’s disease (PD). This study aims to examine the prevalence of MCI among hospitalized older adults with PD, preliminarily identify related factors, and explore its possible clinical impact, with the goal of providing evidence to inform more targeted screening and intervention strategies.MethodsA cross-sectional survey was conducted in China. From July 2022 to January 2025, a total of 339 hospitalized older adults with PD were recruited from a hospital using convenience sampling. Data were collected on demographic characteristics, biochemical markers, and clinical assessments. MCI was evaluated using the Mini-Mental State Examination. Univariate analysis was conducted to examine potential associations between MCI and the collected variables. Multivariate logistic regression was then used to identify independent factors and their impact associated with MCI in hospitalized older adults with PD.ResultsThe results showed that the prevalence of MCI in hospitalized older adults with PD was 45.4%. Multivariate logistic regression analysis revealed that MCI in hospitalized older adults with PD was significantly associated with education level of primary and below [OR = 6.358, 95% CI (2.542, 15.902)] and junior [OR = 4.782, 95% CI (1.965, 11.635)], higher MDS-UPDRS-III scores [OR = 1.023, 95% CI (1.007, 1.039)], presence of anxiety [OR = 2.045, 95% CI (1.080, 3.873)], lower hemoglobin levels [OR = 0.983, 95% CI (0.968, 0.998)], and longer hospitalization duration [OR = 1.833, 95% CI (1.113, 3.017)].ConclusionOur study observed a relatively high prevalence of MCI among hospitalized older adults with PD, and identified several associated factors, including lower educational level, greater severity of motor symptoms, anxiety, and reduced hemoglobin levels. These findings provide preliminary insights into factors that may warrant consideration when designing PD-MCI screening and intervention programs. Notably, we also found an association between PD-MCI and longer hospitalization duration, suggesting that early identification and management of MCI may help improve patient outcomes and reduce hospitalization burden.